Alternations of Septal-hippocampal System in the Adult Wistar Rat with Spatial Memory Impairments Induced by Chronic Cerebral Hypoperfusion - Choi, Bo-Ryoung (The Korean Society for Brain and Neural Science, 2011)
In the current investigation, the status of the septo-hippocampal cholinergic pathway and hippocampal mitogen-activated protein kinase (MAPK) signaling was examined in male Wistar rats with chronic cerebral hypoperfusion, which showed cognitive deficits based on assessment on a version of the Morris water maze. Chronic cerebral hypoperfusion was induced by bilateral common artery occlusion and maintained for 12 weeks until behavioral testing. Chronic cerebral hypoperfusion was shown to induce memory impairments and microglial activation in regions of white matter, including the fimbria of hippocampus. Choline acetyltransferase expression of the basal forebrain and expression of hippocampal MAPKs was decreased in rats with BCCAo compared to control rats. The results of this study suggest that cognitive decline induced by chronic cerebral hypoperfusion could be related to dysfunction of the basal forebrain cholinergic system and reduction of hippocampal MAPK activities.